HUBUNGAN TINGKAT PENGETAHUAN DENGAN KEPATUHAN PENGGUNAAN ALAT PELINDUNG DIRI (APD) PADA PEKERJA MEKANIK DI AREA WORKSHOP PT. XYZ KOTA SURABAYA - Friska Ayu; Muslikha Nourma R; Merry Sunaryo (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2017)
Along with the rapid development of industry encourages the increasing use of machinery, work equipment in the process of produsi with accompanied the application of techniques and technology from various levels in all sector. This means that there maybe a high risk of accidents due to work and also an increase in the amount of intensity of hazard sources in the workplace. Using of Personal Protective Equipment (PPE) is the final stage of hazard control, although the use of PPE will be maximized if other controls such as elimination, substitution, enginee was already applied. This research was conducted at PT.XYZ which is one of the companies engaged in the delivery of goods through sea lanes located in Tanjung Perak, Surabaya by using analytical observational method with a cross sectional study design with a total sample of 38 people. The characteristics of the respondents and the level of compliance with the use of PPE were obtained from interviews with mechanicalworkers in the workshop area. From the results of interviews conducted, as many as 24 mechanical workers obedient in using PPE and 14 others are not obedient in using PPE. The result of statistical test using chi square test shows that there is correlation between knowledge level (p = 0,002) with level of compliance of PPE usage on mechanical worker in workshop area. Advisable for workers to further improve compliance and self-awareness in using personal protective equipment (APD) whileworking or while in the work environment because its relates to the personal health and safety of workers. For the company should be more firm in supervising the worker in this case about the habit of using personal protective equipment in accordance with the policy set.